Quantification of V, Ni, Zn and Fe in Asphalt by Atomic Absorption Spectroscopy - Hidalgo Porras, Jocseline M. (2025)
Asphalt has complex chemical and physical compositions that normally vary with the source of crude oil. Its composition is based on approximately 84% C, 10% H2, 1% O2 and 5% trace elements such as S, Ni, V and Fe. This is the development of a new method to quantify V, Ni, Zn and Fe on asphalt AC-30 by atomic absorption spectroscopy. These metals were detected qualitatively with a higher intensity in an X-ray analysis by fluorescence in an electron scanning microscope. Some metals found in asphalt may have a catalytic effect on the oxidation of asphalt.The research proposes a treatment process of up to 2 g of asphalt, which is based on dilution with mineral spirits in volumetric flasks with the aid of an ultrasonic bath to lighten the dilution. The parameters of optimization of the method are dictated by looking for the adequate instrumental data in the atomic absorption equipment to obtain the highest possible absorbance in the alignment of both the burner and the hollow cathode and deuterium lamps; In addition to the optimization of the flame and the flow of the nebulizer. The calibration curves of each metal were performed with a hydrocarbon-based standard to measure metal concentrations in asphalt in mg / kg with a linear correlation coefficient of at least 0,995. The asphalt recovery study is performed with the addition of a quantity of the metals directly to the asphalt matrix aliquots. The concentrations obtained for Ni were 70, V 330, Zn 24 and for Fe 10 ppm, which presented a relative standard deviation of less than 1%, indicating that measurements of the same sample are accurate and have little dispersion between them. The average recoveries were 99,17% for Ni, 100,30% V, 92,26% Zn and 97,72% Fe. These results indicate that the method is reliable for the quantification of metals by the atomic absorption technique; values greater than 100% are given by readings of absorbances higher than expected or by generation of false positives in the technique.